2012
DOI: 10.1007/s10620-012-2273-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Etiologic Factors on Clinical Outcome in Patients with Peptic Ulcer Bleeding

Abstract: The incidence of peptic ulcer bleeding has not changed over a 5-year observational period. The overall 30-day mortality was positively correlated to older age, underlying comorbid illnesses, in-hospital bleeding recurrence and the absence of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…Peptic ulcer bleeding is still the most common cause of nonvariceal upper GI bleeding and there are a lot of studies that have been conducted to identify the risk factors for mortality in those patients [5][6][7]. Although Mallory-Weiss syndrome is a relatively common cause of upper GI bleeding, accounting for up to 15% of cases [8,9], to our knowledge there are no large prospective studies that systematically analyzed the mortality in patients with bleeding Mallory-Weiss syndrome and the risk factors influencing mortality in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Peptic ulcer bleeding is still the most common cause of nonvariceal upper GI bleeding and there are a lot of studies that have been conducted to identify the risk factors for mortality in those patients [5][6][7]. Although Mallory-Weiss syndrome is a relatively common cause of upper GI bleeding, accounting for up to 15% of cases [8,9], to our knowledge there are no large prospective studies that systematically analyzed the mortality in patients with bleeding Mallory-Weiss syndrome and the risk factors influencing mortality in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…The factors considerably affecting the rebleeding rate were hemodynamic instability upon admission, moderate to severe comorbidities, and the presence of duodenal ulcer larger than 2 cm in diameter with a spurting bleeding ( 5 ). Causes of mortality after APUH are more often related to cardiac or multiorgan failure than to the bleeding itself, particularly in older and co-morbid patients ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the prevalence of H. pylori infection declines, there is an increase in the proportion of patients with ulcer hemorrhage unrelated to H. pylori infection or the use of non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin ( 4 ). Recent data suggest that patients with non- H. pylori -non-NSAID idiopathic bleeding peptic ulcers have significantly higher mortality rates than patients with H. pylori ulcers ( 5 ). Numerous studies have shown that endoscopic and pharmacological treatment of APUH episodes can reduce rebleeding rates, rates of surgical interventions, and length of hospital stay, although some trials indicate that none of these approaches has substantially reduced the overall mortality associated with bleeding events ( 3 , 4 , 6 ).…”
mentioning
confidence: 99%
“…Ljubi i N i saradnici su u svom istraživanju dokazali da ulkus duodenalne lokalizacije dijametra ve eg od 2 cm doprinosi hemodinamskoj nestabilnosti i rekurentnom krvarenju. [36] Rezultati koji su podudarni sa našim prezentovani su u studiji Jensen D. Prate i specifi an endoskopski nalaz u ovoj studiji dokazani su loš prognosti ki ishod i teže forme krvarenja klasifikovane Forrestovom podelom u slu ajevima duodenalnog ulkusa lokalizovanom na zadnjem zidu / ili donjem bulbusa duodenuma, u slu ajevima ulkusne lezije dijametra > od 1,5 cm, kao i dubokih ulkusnih lezija (>3-4 mm). [37] U našem radu 79/54,9% krvare ih duodenalnih ulkusa le eno je endoskopski, 30/20,8% konzervativno, dok je 35/24,8% le eno hirurški.…”
Section: Diskusijaunclassified